2006
DOI: 10.1212/01.wnl.0000203129.82104.07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential CSF biomarkers in ALS

Abstract: Additional application of a "three-protein" biomarker model to current diagnostic criteria may provide an objective biomarker pattern to help identify patients with ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(141 citation statements)
references
References 27 publications
(32 reference statements)
5
136
0
Order By: Relevance
“…Immobilization, disuse or denervation triggers muscular atrophy, which clearly shows that neuromuscular innervation patterns are directly linked to gene expression, protein abundance and isoform patterns in skeletal muscles [29]. In analogy to the recent proteomic profiling of cerebrospinal fluids from patients suffering from ALS and the spinal cord from the wobbler mouse [19][20][21][22][23], this study describes the findings of the MS-based proteomic survey of skeletal muscle from the WR mouse. From the detailed analysis of the isoform patterns of the sarcomeric MyHCs it became clear that the response of gene expression in skeletal muscle to denervation is characteristically different from that to hyper-excitability and muscular dystrophy [28].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Immobilization, disuse or denervation triggers muscular atrophy, which clearly shows that neuromuscular innervation patterns are directly linked to gene expression, protein abundance and isoform patterns in skeletal muscles [29]. In analogy to the recent proteomic profiling of cerebrospinal fluids from patients suffering from ALS and the spinal cord from the wobbler mouse [19][20][21][22][23], this study describes the findings of the MS-based proteomic survey of skeletal muscle from the WR mouse. From the detailed analysis of the isoform patterns of the sarcomeric MyHCs it became clear that the response of gene expression in skeletal muscle to denervation is characteristically different from that to hyper-excitability and muscular dystrophy [28].…”
Section: Resultsmentioning
confidence: 97%
“…The current international effort to discover reliable biomarkers of ALS [16] includes the verification of both suitable metabolites [17] and protein factors [18]. Recent proteomic profiling studies of ALS patient samples and the WR animal model have focused on the analysis of cerebrospinal fluid [19][20][21] and cervical and lumbar spinal cord [22,23], respectively. The studies on the WR mouse showed that the majority of differentially expressed proteins were related to the glutamate-glutamine cycle, energy transduction, redox functions and astrogliosis [22], thus confirming previous studies [24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous efforts in our group, as well as others, identified cystatin C as a potential biomarker in the CSF of patients with ALS [49,[97][98][99][100]. Cystatin C is a cysteine protease inhibitor that is involved in extracellular matrix (ECM) regulation, as well as a variety of CNS diseases [101,102].…”
Section: Cystatin Cmentioning
confidence: 98%
“…12 The derived granin fragments are detectable in cerebrospinal fluid (CSF), thus making them attractive as potential biological markers of the neuronal regulatory secretory pathway. 13 Altered (mainly reduced) CSF concentrations of different granins have previously been reported in studies of neurologic disorders like Alzheimer disease, 14 multiple sclerosis, 15 amyotrophic lateral sclerosis, 16 frontotemporal dementia 17 and schizophrenia. 18 A role of chromogranins in psychiatric disorders has been further suggested by genetic [19][20][21][22] and postmortem brain studies of patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 80%